2004
DOI: 10.1111/j.1365-2567.2004.01914.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cleavage sites for polymeric immunoglobulin receptor

Abstract: SUMMARYHuman polymeric immunoglobulin receptor (pIgR) was expressed in baby hamster kidney (BHK) cells using a recombinant vaccinia virus transfection system. Cleavage of pIgR on the cell surface was partially inhibited by the proteinase inhibitor, leupeptin. We addressed the question whether some particular regions of pIgR could affect the efficient cleavage of this molecule, with the following results: (1) a mutant lacking the entire cytoplasmic region resulted in release of secretory component (SC) into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Most newly synthesized ∆CL mutant was secreted in the culture media, and no mutant pIgR was detected in the cell lysates (67). Our results further suggest that the cytoplasmic deletion mutant of pIgR was released from the cells immediately after its synthesis and that the cytoplasmic portion of pIgR has a plasma membrane retention signal (67).…”
Section: Basolateral Sortingsupporting
confidence: 54%
See 4 more Smart Citations
“…Most newly synthesized ∆CL mutant was secreted in the culture media, and no mutant pIgR was detected in the cell lysates (67). Our results further suggest that the cytoplasmic deletion mutant of pIgR was released from the cells immediately after its synthesis and that the cytoplasmic portion of pIgR has a plasma membrane retention signal (67).…”
Section: Basolateral Sortingsupporting
confidence: 54%
“…5, ∆CL mutant) and observed that fSC release was drastically inhibited. These results indicate that domain 6 of pIgR has an intrinsic signal for the pIgR to be recognized and cleaved by proteolytic enzyme (67). The 12 amino acids spanning from Pro589 to Asp600 are highly conserved in several species and are the putative cleavage site of pIgR (31).…”
Section: Pigr Cleavagementioning
confidence: 72%
See 3 more Smart Citations